2015
DOI: 10.3109/19401736.2015.1079891
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of the Himalayan honey bee, Apis laboriosa

Abstract: The complete mitochondrial genome of Himalayan bee Apis laboriosa, from Mizoram, India, has been sequenced using Illumina NextSeq500 platform and analysed. The mitogenome was assembled and found to be 15 266 bp in length and the gene arrangement is similar to other honey bee species. The A. laboriosa mitogenome comprises of 13 protein-coding genes (PCGs), 22 tRNAs, 2 rRNAs and an A + T-rich region of 346 bp. Based on the concatenated PCGs, in the phylogenetic tree, A. laboriosa is placed as a sister group alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The topology of the resulting species tree ( fig. 1 F ) was consistent with the phylogenies in previous studies ( Arias and Sheppard 2005 ; Kapheim et al 2015 ; Chhakchhuak et al 2016 ; Branstetter et al 2017 , 2018 ; Diao et al 2018 ).…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…The topology of the resulting species tree ( fig. 1 F ) was consistent with the phylogenies in previous studies ( Arias and Sheppard 2005 ; Kapheim et al 2015 ; Chhakchhuak et al 2016 ; Branstetter et al 2017 , 2018 ; Diao et al 2018 ).…”
Section: Methodssupporting
confidence: 91%
“…To comprehend its evolutionary dynamics and adaptations to the local environment, A. laboriosa is usually compared with the closely related species Apis dorsata , a lowland giant honeybee that is widespread throughout tropical and subtropical Asia. These two species were grouped into a “giant honeybees” clade in previous phylogenetic studies ( Willis et al 1992 ; Engel and Schultz 1997 ; Arias and Sheppard 2005 ; Chhakchhuak et al 2016 ). Although A. dorsata genome has been sequenced recently ( Oppenheim et al 2020 ), whole-genomic data for A. laboriosa are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The Nagaland Beekeeping and Honey Mission (NBHM) has collated information on the "Rock bee" within the state of Nagaland (Team NBHM 2015). Similarly, Chhakchhuak et al (2016) reported a nesting cliff in Murlen in Mizoram.…”
Section: Data Collectionmentioning
confidence: 92%
“…1). Several genetic analyses indicate these two taxa have diverged sufficiently to consider A. laboriosa to be a distinct species (Arias and Sheppard 2005;Raffiudin and Crozier 2007;Lo et al 2010;Chhakchhuak et al 2016;Takahashi et al 2018). Despite these many differences, Engel (1999), in the most recent reassessment of Apis taxonomy, considered A. laboriosa to be a subspecies of A. dorsata that may be deserving of species status.…”
Section: Identification Of Apis Laboriosamentioning
confidence: 99%